Pathogenicity of Entomopathogenic Nematodes (NEP) Results of In Vitro Propagation Using Egg Yolk Media Against Mustard Caterpillar Plutella xylostella - Mohamad Hipti; Wiludjeng Widajati; Sri Wiyatiningsih; Ramadhani Mahendra Kusuma (Nusantara Science and Technology Proceedings, 2021)
Decreased mustard plant production is inseparable from the presence of plant pests and disease, one of which is Plutella xylostella. This pest can reduce the yield by 30-40%, even in some cases found to experience crop failure. Generally, in the community, controlling pests is using chemical pesticides. However, excessive use of chemical pesticides harms the environment and triggers health problems in humans, So, biological control is needed. One of them is an entomopathogenic nematode (NEP). Advantages Nematodes are environmentally friendly and are fast in crippling their host, but the multiplication of entomopathogenic nematodes encounters many obstacles, so research on these alternatives is needed. This research was carried out to determine the pathogenicity of entomopathogenic Nematodes cultured from the egg yolk media on Plutella xylostella larvae, then developed as an effective biocontrol. The pathogenicity test for Plutella xylostella larvae was performed using nine treatments placed in a factorial Completely Randomized Design (CRD) with each treatment repeated three times. The study indicate that the four bacterial isolates had the same ability to kill Plutella xylostella larvae during four days of observation, with the greatest percentage of 100 percent and the lowest percentage of 76.7 percent.